Baicalein Alleviates Osteoarthritis Progression in Mice by Protecting Subchondral Bone and Suppressing Chondrocyte Apoptosis Based on Network Pharmacology - Yi, Nanxing; Mi, Yilin; Xu, Xiaotong; Li, Naping; Zeng, Fan; Yan, Ke; Tan, Kaiyun; Kuang, Gaoyan; Lu, Min (Frontiers in Pharmacology, 2022)
As life expectancy increases, Osteoarthritis (OA) is becoming a more frequently seen chronic joint disease. The main characteristics of OA are loss of articular cartilage, subchondral bone sclerosis and synovial inflammation. Baicalein (Bai), a traditional Chinese medicine extracted from Scutellaria baicalensis Georgi, has been demonstrated to exert notable anti-inflammatory effects in previous studies, suggesting its potential effect in the treatment of OA. In this study, we first predicted the action targets of Bai, mapped target genes related to OA, identified potential anti-OA targets for Bai, performed gene ontology (GO) enrichment and KEGG signaling pathway analyses of the action targets, and analyzed the molecular docking of key Bai targets. Additionally, the effect and potential mechanism of Bai against OA were verified in mouse knee OA models induced by destabilized medial meniscus (DMM) surgery. GO and KEGG analyses showed that 19 anti-OA targets were mainly involved in the response to oxidative stress, the response to hypoxia and apoptosis, and the PI3K-Akt and p53 signaling pathways. Molecular docking results indicated that BAX, BCL 2 and Caspase 3 enriched in the apoptotic signaling pathway have high binding affinity with Bai. Validation experiments showed that Bai can significantly attenuate the loss of articular cartilage (OARSI score), suppress synovial inflammation (synovitis score), and ameliorate subchondral bone resorption measured by micro-CT. In addition, Bai notably inhibited the expression of apoptosis-related proteins in articular cartilage (BAX, BCL 2 and Caspase 3). By combining network pharmacology with experimental validation, our study identifies and verifies the importance of the apoptotic signaling pathway in the treatment of OA by Bai. Bai may have promising application and potential therapeutic value in OA treatment.